Health Related Quality of Life and Associated Factors of Inflammatory Bowel Disease Outpatient Unit in Dr. Cipto Mangunkusumo Hospital - Afistianto, Muhammad Fikri; Simadibrata, Marcellus; Putranto, Rudi; Abdullah, Murdani; Setiati, Siti; Wisnu, Wismandari; Antono, Dono; Susilo, Adityo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Inflammatory Bowel Disease (IBD), encompassing ulcerative colitis (UC) and Crohn's disease (CD), is an inflammatory digestive tract condition with unknown causes. Its unpredictable symptoms affect quality of life. In Indonesia, the quality of life of IBD patients remains unreported. Factors such as advanced age, long disease duration, active disease, corticosteroid use, comorbidities, unemployment, and poor sleep quality may reduce quality of life. This study aims to assess the quality of life profile of IBD patients and its associated factors.Methods: This cross-sectional study collected data from October to November 2024 through interviews at the outpatient unit of Dr. Cipto Mangunkusumo Hospital (RSCM). Quality of life was measured using the Inflammatory Bowel Disease Questionnaire 9 (IBDQ-9), and sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI). Both tools were validated in Indonesian. Eligible participants met inclusion and exclusion criteria. Bivariate and multivariate logistic regression analyses identified factors associated with quality of life.Results: Among 201 participants, 95% reported a good quality of life. Multivariate analysis identified active disease (PR 4.072 [1.133–14.633], p = 0.031) and combination therapy (PR 12.803 [1.423–115.147], p = 0.023) as factors associated with poor quality of life. Age, disease duration, comorbidities, employment status, and sleep quality showed no significant associations.Conclusion: Most IBD patients (95%) in the RSCM outpatient unit reported a good quality of life. Active disease and combination therapy were linked to poorer quality of life.